SENSORLESS SPEED ROTOR FLUX ORIENTED CONTROL OF THREE PHASE INDUCTION MOTOR - Pjetri, Alfred; Luga, Ymer; Bardhi, Astrit (European Scientific Journal, ESJ, 2015)
Sensorless speed rotor flux oriented control of induction motor drives it is known to produce high performance because of decoupling rotor flux and torque producing current components of stator currents. This paper describes a simple and robust sensorles speed rotor flux oriented control system for three phase induction motor drives that it is adequate for high dynamic applications. To control the rotor speed of the induction motor drives, a PI controller is included in the speed control system. A hysteresis current controllers are applied for changing the magnitude and the frequency of the output voltage of the PWM voltage source inverter which fed the induction motor. In order to verify the proposed sensorlees speed control system, the model of the system is implemented in MATLAB Simulink software, which is suitable for testing the dynamic simulation. Simulation results shows that the reference and rotor speed of induction motor are very closed to each-other under step load torque changes.